2015
DOI: 10.1186/s13612-015-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Positive Instruction in Music Studios: Introducing a New Model for Teaching Studio Music in Schools Based upon Positive Psychology

Abstract: This practice paper explores the intersection of school studio-music pedagogy and positive psychology in order to enhance students’ learning and engagement. The paper has a practitioner focus and puts forward a new model of studio teaching, the Positive Instruction in Music Studios (PIMS) model that guides teachers through four key positive psychology processes that can be used in a music lesson: positive priming, strengths spotting, positive pause, and process praise. The model provides a new, positively orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(54 reference statements)
1
14
0
1
Order By: Relevance
“…However, we also discover some disadvantages and insufficiencies of the software in practical teaching process along with their wide application. Thus, the research in this paper bases on construction of the interactive solfeggio teaching reposi-tory suitable for music discipline education and music quality education of our country, so as to provide teachers and students with the window for autonomous resource management and learning and make it possible to introduce the music appreciation works with Chinese multi-ethnic characteristics as many as possible [6].…”
Section: Literature Reviewsupporting
(Expert classified)
“…However, we also discover some disadvantages and insufficiencies of the software in practical teaching process along with their wide application. Thus, the research in this paper bases on construction of the interactive solfeggio teaching reposi-tory suitable for music discipline education and music quality education of our country, so as to provide teachers and students with the window for autonomous resource management and learning and make it possible to introduce the music appreciation works with Chinese multi-ethnic characteristics as many as possible [6].…”
Section: Literature Reviewsupporting
(Expert classified)
“…There are few other studies in the literature investigating the effect of encouraging positive functioning and positive emotion on music performance. Broomhead, Skidmore, Eggett, and Mills (2012) found that positive priming, in which the trigger words "bold", "confident" and "free" were repeated silently pre-performance, was effective in aiding expressive performance in junior high school singers, and Patston and Waters (2015) proposed a model of music teaching based on Seligman's (2011) PERMA model of well-being, which includes the use of positive priming, strengths spotting and the positive pause ("what went right" as opposed to the more frequently used "what went wrong" approach), however this model has not yet been empirically investigated. Although there are investigations describing professional classical musicians' well-being using the framework of Seligman's PERMA model (Ascenso, Williamon, & Perkins, 2017), there has been little investigation of the use of the PERMA model as a possible framework for facilitating optimal performance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recognition of the high prevalence of MPA (Kenny et al, 2014) and acknowledgement of the need for courses on music performance skills during musical training (Brodsky, 1996;Wrigley & Emmerson, 20113), few musical educational institutions provide such courses (Clark & Williamon, 2011). Those few existing courses tend to focus on reducing pathological MPA rather than a positive psychology approach that focuses on enhancing positive functioning (Patston & Waters, 2015). Investigations of the efficacy of existing methods for treating MPA indicate that Cognitive Behavioural Therapy based interventions are most effective (for an overview, see Burin & Osorio, 2016).…”
Section: Interventions For Improving Music Performancementioning
confidence: 99%
“…It also highlights the pressure that children sometimes face in music instruction, participating in examinations and being subjected to direct criticisms from families, teachers, and even strangers. Some researchers have proposed that educators could play a significant role in guiding children through MPA (Fehm & Schmidt, 2006;Patston, 2014;Patston & Waters, 2015;Sarikaya & Kurtaslan, 2018). Patston (2014) and Patston and Waters (2015) suggest that, instead of pushing students to practice for extended periods with unrealistic performance expectations, educators should be encouraged to engage with students by creating individualized lessons and practice plans to support effective and equitable learning for their students.…”
Section: Mpa and Perfectionismmentioning
confidence: 99%